Care and treatment for primary cutaneous lymphoma-associated ulcers: Two case reports - Min Wei; Jun Wei; Jian Li; Ruyue Li; Jing Liu (SAGE Open Medical Case Reports)
Primary cutaneous lymphoma is a heterogeneous group of cutaneous lymphocytic primary tumors belonging to the extranodal category of non-Hodgkin lymphoma. Skin is the second most common site of extranodal non-Hodgkin lymphoma after the gastrointestinal tract. Skin lesions are the main manifestations of primary cutaneous lymphoma. Here, we report two successful cases of skin ulcers caused by primary cutaneous lymphoma, which is both rare and difficult to diagnose. One case involved primary cutaneous T-cell lymphoma, and the other involved primary cutaneous B-cell lymphoma. Systemic antitumor therapy combined with the right local wound management is the key to ulcer healing. For wound management, in addition to infection control, exudate management, pain control, and odor management, evaluation and intervention of debridement are worthy of consideration, but they must be evaluated by an expert group, and plans must be made for bleeding. Finally, the wounds of the two patients were completely healed after 79 and 65 days under active systemic therapy.